Pelatihan Operasional Dasar Mikroskop dan Pengenalan Alat Laboratorium pada Mahasiswa Pendidikan Biologi Universitas Pendidikan Mandalika - Dharmawibawa, Iwan Doddy; Nofisulastri, Nofisulastri; Royani, Ida; Imran, Ali (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2023)
Microscope is one of the supporting media in learning Biology. With a microscope objects or organisms that are unable to be seen by the human senses can be observed clearly. The aim of this program is to increase the qualifications and capacity of Biology Education Students through increasing knowledge and skills in using and caring for microscopes. The target of this activity is first semester students of the Biology Education Study Program, Faculty of Science, Engineering and Applied, Mandalika University of Education. The methods used are lectures, discussions, questions and answers and demonstrations using a microscope properly. The results achieved were that participants were able to use a microscope to observe objects and were able to take care of the microscope after use. Participants looked very enthusiastic and interested because they were able to observe plant tissue directly under a microscope. It can be concluded that the basic operational training activities for microscopes and the introduction of laboratory tools were able to increase the participants' knowledge and skills from every aspect measured.